Effect of level of expansion and inertia level in a suddenly expanded flow - Chaudhary, Zakir Ilahi; Shinde, V.B; Ashfaq, Syed; Khan, Sher Afghan (2015)
An experimental study has been carried out to assess the effectiveness of the active control in the form of micro jets to control the base pressure in a suddenly expanded axi-symmetric duct. Four micro jets of 1mm orifice diameter located at 90 intervals along a pitch circle diameter of 1.3 times the nozzle outlet diameter in the base region are employed as active controls. The Mach numbers of the present study are 2.5 and 3.0. The jets are expanded suddenly into an axi-symmetric circular tube with four cross-sectional area 2.56, 3.24, 4.84 and 6.25 times that of nozzle exit area. The Length to Diameter ratio of the suddenly expanded duct is varied from 10 to 1 and experiments are conducted for Nozzle Pressure Ratio (NPR) from 3 to 11. Since the jets remain over expanded for all the NPRs of the present study, even though, with increase in the NPR, the level of over expansion will decrease. It is well known that for over expanded nozzles an oblique shock will be formed at the nozzle lip, which in turn will result in the increase of the base pressure once it passes through the shock wave. From the results it is observed that for the NPRs 3 and 5 there is no appreciable gain in the base pressure, and hence, control employed in the form of micro jets is not effective, however, at NPR 7, 9, and 11 there is remarkable change in the base pressure values. This clearly indicates that the level of expansion plays a significant role to decide on the value of the base pressure and the control effectiveness of the micro jets. It is found that the micro jets can serve as an effective controller of base pressure in a suddenly expanded duct. The micro jets do not adversely influence the wall pressure flow field in the enlarge duct.